Massive Left Atrial Thrombus After a Left Atrial Surgical Ablation and Bioprosthetic Mitral Valve Replacement. Issue 4 (July 2020) - Husaini, Mustafa; Quader, Nishath; Braverman, Alan C.; Damiano, Ralph J.; Maniar, Hersh S.
Variability exists regarding the timing and duration of anticoagulation after surgical ablation for atrial fibrillation and bioprosthetic mitral valve replacement (MVR). We report a case in which a patient developed a massive left atrial (LA) thrombus after MVR and left-sided radiofrequency ablation (LRFA). Despite acutely elevated gradients across the bioprosthetic valve, the patient remained asymptomatic and hemodynamically stable; thus, a multidisciplinary, patient-centered discussion was had and the patient was treated successfully with oral anticoagulation.